The difficile in Clostridium difficile infection. (December 2018) - Akoghlanian, Garabet; Lakshmi, Seetha
Highlights: Discussion of the new changes in C. difficile testing algorithm with illustrative table. Emphasis on processes that could facilitate implementation of the new C. difficile testing algorithm. Highlight the changes in the management of C. difficile infection.